2021
DOI: 10.3390/v13122523
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Role of the Expression of Latent-Membrane Protein 1 of Epstein–Barr Virus in Classical Hodgkin Lymphoma

Abstract: The prognostic impact of the presence of Epstein–Barr virus (EBV) in classical Hodgkin lymphoma (cHL) is controversial. Previous studies reported heterogeneous results, rendering difficult the clinical validation of EBV as a prognostic biomarker in this lymphoma. The objective of this study was to evaluate the survival impact of the expression of EBV Latent-Membrane Protein 1 (EBV-LMP1) in tumoral Hodgkin–Reed–Sternberg (HRS) cells of primary diagnostic samples of cHL. Formalin-Fixed Paraffin-Embedded (FFPE) l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…In the subgroup analysis by disease distribution on six continents, the African subgroup showed that EBV-positive patients had a borderline better OS (HR=0.408, 95% CI: 0.147-1.129; P =0.084). For age distribution, some articles ( 16 , 18 , 25 , 28 , 41 , 48 , 50 , 52 ) had sufficient age-stratified survival data, so we combined their HR by a random effects model (I 2 = 62.9%, P=0.003), which was 1.080 (95% CI: 0.657-1.776; P=0.762). In the subgroup of children and adolescents, the pooled HR showed that EBV positivity in HL was correlated with a favorable outcome for OS (HR=0.296, 95% CI: 0.085-1.034, P=0.056), while a significantly poorer OS was associated with EBV positivity in studies covering older adults (HR=1.905, 95% CI: 1.380–2.629; P<0.001).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the subgroup analysis by disease distribution on six continents, the African subgroup showed that EBV-positive patients had a borderline better OS (HR=0.408, 95% CI: 0.147-1.129; P =0.084). For age distribution, some articles ( 16 , 18 , 25 , 28 , 41 , 48 , 50 , 52 ) had sufficient age-stratified survival data, so we combined their HR by a random effects model (I 2 = 62.9%, P=0.003), which was 1.080 (95% CI: 0.657-1.776; P=0.762). In the subgroup of children and adolescents, the pooled HR showed that EBV positivity in HL was correlated with a favorable outcome for OS (HR=0.296, 95% CI: 0.085-1.034, P=0.056), while a significantly poorer OS was associated with EBV positivity in studies covering older adults (HR=1.905, 95% CI: 1.380–2.629; P<0.001).…”
Section: Resultsmentioning
confidence: 99%
“…Five studies ( 39 , 47 , 50 52 ) were included to analyze the impact of EBV infection on PFS. There was significant between-study heterogeneity (I 2 = 54.5%, P=0.066), and the pooled estimate by the random-effects model showed that no significant association was found between EBV positivity and PFS (HR=1.302, 95% CI: 0.881–1.926, P=0.186; Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The prognostic role of LMP1 expression in cHL was evaluated in several studies. The expression of LMP1 as a marker of EBV infection in HL is associated with the mixed-cellularity subtype of cHL and a high-risk international prognostic score [ 53 ]. According to Hu et al (2022), and their systematic review and meta-analysis of 42 qualified studies involving 9570 HL patients, there was an association between EBV positivity and significantly poorer overall survival, particularly in older patients [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…EBV, a gamma-herpesvirus (also known as human herpesvirus 4), is one of the bestexamined examples of a cancer-inducing virus [8]. In a study conducted on patients with classical Hodgkin lymphoma (cHL), the prognostic function of the expression of latent membrane protein 1 of EBV (EBV-LMP1) in cHL was notably unveiled by Santisteban-Espejo and colleagues [9]. The authors also indicated that the treatment protocol based on chemotherapy medications might affect the prognostic role of EBV in cHL.…”
mentioning
confidence: 99%